2010
DOI: 10.1371/journal.pone.0010797
|View full text |Cite
|
Sign up to set email alerts
|

Torpor on Demand: Heterothermy in the Non-Lemur Primate Galago moholi

Abstract: BackgroundHibernation and daily torpor are energy- and water-saving adaptations employed to survive unfavourable periods mostly in temperate and arctic environments, but also in tropical and arid climates. Heterothermy has been found in a number of mammalian orders, but within the primates so far it seems to be restricted to one family of Malagasy lemurs. As currently there is no evidence of heterothermy of a primate outside of Madagascar, the aim of our study was to investigate whether small primates from mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…Many of these primates undergo periods of torpor or heterothermy to conserve energy to cope with low ambient temperatures [25], [26], [27], [28], [29], [30], [31]. Fernández-Duque et al [68] reported that the activity of a lunar philic primate was reduced during cooler temperatures, despite luminance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these primates undergo periods of torpor or heterothermy to conserve energy to cope with low ambient temperatures [25], [26], [27], [28], [29], [30], [31]. Fernández-Duque et al [68] reported that the activity of a lunar philic primate was reduced during cooler temperatures, despite luminance.…”
Section: Discussionmentioning
confidence: 99%
“…Torpor and hibernation have been studied extensively in these species, showing some of the most remarkable specialisations of any nocturnal mammal, such as extreme lowering of the body temperature, and heavy storage of fat in the tail [29], [30]. Torpor has also been observed in a captive sub-adult Galago moholi [31], although it was not observed in two long-term field studies of this species [15], [21], [32]. Indeed, the opposite was the case, when galagos became active in the daytime to feed on valuable gum resources [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the evolution of energy-saving metabolic strategies, particularly in small-bodied primates, could be seen largely as a result of selective environmental forces during major climatic changes in the history of Madagascar. In favor of the traditional position, Nowack et al (2010) point out that hibernation is expressed in members of all major mammalian lineages, and that some expression of heterothermy (albeit not true hibernation) has been reported in the sister taxa of lemurs, the galagos and lorises. Heterothermy, according to this view, is a plesiomorphic trait present in the ancestral strepsirrhine (Dausmann et al 2012).…”
Section: The Evolutionary Context Of Hibernation In Lemursmentioning
confidence: 97%
“…The traps were set late in the afternoon and checked hourly between 17:00 h and 05:00 h. All individuals spent ≤ 1 hour within a trap before removal. After removal, trapped individuals were aged, sexed, weighed and body length was measured from nose to the base of the tail with a flexible measuring tape following Nowack et al (2010), and all fresh faeces within the traps were collected. Individuals were handled for less than five minutes, without the use of anaesthesia, before being released at the exact spot of capture.…”
Section: Trapping and Faecal Sample Collectionmentioning
confidence: 99%
“…We then averaged the ten IORs to achieve an average IOR between the two observers (89.9 ± SE 0.03 %). Although free-ranging populations from both sites were accustomed to humans, due to previous biological studies (NNR; Mzilikazi et al 2006;Nowack et al 2010;Nowack et al 2013;Pullen et al 2000) or frequent human interaction (OP), observers were never closer than five metres to an individual being followed.…”
Section: Ad Libitum Followsmentioning
confidence: 99%